Structural evolution and phase transition of uniaxially stretched poly(butylene adipate-co-butylene terephthalate) films as revealed by in situ synchrotron radiation small and wide angle X-ray scattering. Issue 1 (27th November 2018) - Li, Lifu; Ji, Youxin; Zhang, Qianlei; Zhao, Haoyuan; Ali, Sarmad; Chen, Pinzhang; Xia, Zhijie; Chen, Wei
Abstract : Structural evolution and phase transition of poly(butylene adipate- co -butylene terephthalate) during uniaxial stretching. Abstract : Poly(butylene adipate- co -butylene terephthalate) (PBAT) films under uniaxial stretching at room temperature were characterized by in situ synchrotron radiation wide-angle X-ray scattering (WAXS) and small-angle X-ray scattering (SAXS). Based on the macroscopic stress–strain curve and the microscopic structural information obtained by SAXS/WAXS, three regions are defined. In region I, the molecular chain of the amorphous region undergoes elastic deformation, namely affine deformation. After the yielding point (region II), the oriented amorphous chain starts to crystallize into the metastable β -crystal. In region III, where the strain-hardening happens, the transition from α -crystal to β -crystal occurs through a solid–solid transition mechanism. Therefore, the β -crystal is found to be formed through two different pathways during stretching. Meanwhile, it can be observed that the change in transmittance and phase transition are almost synchronous. This is attributed to the similarity of the refractive index of both the amorphous and crystalline regions after stretching. The relationship between the PBAT phase transition and its optical properties is revealed on the microscopic scale and could provide theoretical guidance for the preparation of agricultural films with higher transmittance.